Monitoring electron transfer by photoacoustic spectroscopy - Cornélio, M. L. [UNESP] (1995)
The electron transfer process between octaethylporphin and quinone molecules dispersed in a polymeric matrix was studied by the photoacoustic technique. It was observed that there was an enhancement of the octaethylporphin photoacoustic signal with an increase of the quinone concentration in the films. This increase appeared to be complementary to octaethylporphin fluorescence quenching and was associated with the electron transfer process. The data were analyzed according to the theory developed by Kaneko for fluorescence data (Kaneko 1992). © 1995 Springer-Verlag.